PENGARUH KUALITAS PELAYANAN PERPAJAKAN TERHADAP KEPUASAN WAJIB PAJAK, KEPATUHAN WAJIB PAJAK DAN PENERIMAAN PAJAK (STUDI PADA KANTOR PELAYANAN PAJAK MADYA MALANG) - Silalahi, Sixvana (Jurnal Mahasiswa Perpajakan, 2015)
The purpose of this research is to know how to influence the quality of service taxation against the satisfaction of the Taxpayers and compliance of the Taxpayers, as well as to know the influence of the satisfaction of the Taxpayers and compliance of the Taxpayers against tax revenues. One of the reformation that have been done by Directorate General of Tax is to change the system and the tax collection mechanism of the official assessment becomes self assessment system. The decision was implemented on the 1st January 1984 with the enacment of law No. 6 of 1983 on General Provision and Taxation Procedures (KUP). To support this system in order to run smoothly, then the required quality of service is excellent. Keyword: Self Assessment System, Dimension of Service Quality, Quality of Taxation Service, Satisfaction of the Taxpayers, Compliance of the Taxpayers, Tax Revenue.